2009
DOI: 10.1016/j.applthermaleng.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle geometry effects in liquid jet array impingement

Abstract: The use of impinging liquid jets in electronics thermal management is attracting some consideration due to their very high heat transfer coefficients, hot spot targeting capabilities and moderate hydraulic power requirements. In this investigation an experimental study of the cooling capabilities of impinging water jet arrays is presented. Of particular interest here is the influence that the inlet and outlet geometries have on the thermal-hydraulics of jet impingement heat transfer with the aim of determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The characteristics of ceiling jet, such as heat transfer and temperature profile etc., have received extensive attention in certain thermal engineering research for large industrial or commercial storage facilities and tunnels [4][5][6][7][8][9][10][11][12][13][14][15][16]. Studies quantifying the flow of hot gases under a ceiling resulting from the impingement of a fire plume have M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT been conducted since 1950s, in which the theoretical models came from the work carried out by Alpert [10] and by Heskestad and Delichatsios [11].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of ceiling jet, such as heat transfer and temperature profile etc., have received extensive attention in certain thermal engineering research for large industrial or commercial storage facilities and tunnels [4][5][6][7][8][9][10][11][12][13][14][15][16]. Studies quantifying the flow of hot gases under a ceiling resulting from the impingement of a fire plume have M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT been conducted since 1950s, in which the theoretical models came from the work carried out by Alpert [10] and by Heskestad and Delichatsios [11].…”
Section: Introductionmentioning
confidence: 99%
“…The structural exit cross-section of the jet gives varied flow patterns of the jet, which has an effect on cooling ability. It is also true that its practical use is dependent on ease in manufacturing of the jet [18][19][20]. It is observed that slot jet and circular jets are used regularly due to their simplicity in manufacturing and applications.…”
Section: Jet Impingement Reviewmentioning
confidence: 99%
“…7 was found to be in close agreement with that of Fabbri and Dhir [11] albeit the latter work was performed for the impingement of free surface microjets. Recently, Whelan and Robinson [18] showed that the pressure drop penalty could be notably reduced by chamfering the orifice inlet without significantly affecting the heat transfer.…”
Section: Waterblock Designmentioning
confidence: 99%